2015
DOI: 10.3146/0095-3679-42.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Peanut Nodules and Seasonal Nodulation Pattern in Different Tillage Systems Using a Minirhizotron System

Abstract: Nodulation is essential for providing the nitrogen (N) needs of peanut, but little is known about the time course of nodule development with soil depth in a field production system. A minirhizotron system allows for non-destructive, periodic digital imaging of identical locations in the crop root system in situ, including the associated nodules. Because the system allows imaging at the same location over time, individual nodule development and subsequent senescence can be followed throughout the growing season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Barbedo (2012), that also used digital images, obtained a good correlation between automatic and manual counting (0.91). Using a different approach, but also based on digital images, Gray et al (2013) and Rowland et al (2015) used the minirhizotron technique to assess nodulation in legumes. Gray et al (2013) demonstrated the potential of this technique, already used in the observation of root growth, to understand the dynamic of nodule production and distribution in soil profile within the growing season.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Barbedo (2012), that also used digital images, obtained a good correlation between automatic and manual counting (0.91). Using a different approach, but also based on digital images, Gray et al (2013) and Rowland et al (2015) used the minirhizotron technique to assess nodulation in legumes. Gray et al (2013) demonstrated the potential of this technique, already used in the observation of root growth, to understand the dynamic of nodule production and distribution in soil profile within the growing season.…”
Section: Discussionmentioning
confidence: 99%
“…The estimates generated from minirhizotron for nodule number, density and size were consistent with previously published data for fieldgrown soybean. The use of minirhizotron technique also allowed to study for the first time the nodule formation through the soil profile and across the time in peanut (Rowland et al, 2015). Cardoso et al (2009) found out that most of the nodulation resulting from inoculation occurs at the primary crown root of peanut, soybean and common bean.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with conventional tillage, conservation tillage showed a reduced incidence of tomato spotted wilt disease of peanut in North Carolina (Hurt, 2006). The nodule size is larger in conservation tillage compared to conventional tillage (Rowland, 2015). In Georgia, the conservation production system increased water-holding capacity of the soil and enhanced soil water conservation (Hawkins, 2016).…”
Section: Land Preparation and Conservation Tillagementioning
confidence: 99%